ANALYSIS OF VALUE STREAM MAPPING AND LEAN SYSTEM APPLICATION TO IMPROVE TENDER CREATING PROCESS: A CASE STUDY IN PT XYZ INDONESIA - Rachman, Akbar (Emerging Markets : Business and Management Studies Journal, 2018)
PT XYZ Indonesia, established in 1986, is a US-based oil and gas service company who providesservices from drilling and evaluation, to completion and production. As a service company with huge amount field projects, its Business Development division is a spearhead for the company?s growth. Over the years, the competition is getting tougher with many local companies, besides other new international service companies, are penetrating the Indonesia?s market. PT XYZ Indonesia have been utilizing the same procedure and process map to develop its business strategy, win tenders, execute field projects, and ultimately expand its operation. The purpose of this research is to analyze the current process of tender creation; identify the challenges the company has been having to win more projects, and eventually provide an improvement to the current-state map. The qualitative research was done by having field observations, conducting interviews, and analyzing secondary data, to reveal the issues at hand. The results show that PT XYZ Indonesia, especially its Business Development division, is not utilizing its resources to full capacity by not managing it efficiently ? especially in forms of administration and workforce. In conclusion, a set of recommendations to improve the tender creating process specifically, and its Business Development strategy generally, were formulated.